2018
DOI: 10.24874/ti.2018.40.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness and Tribological Wear Behaviour of Micro Alloyed Pearlitic- Ferritic Ductile Cast Iron

Abstract: Fracture toughness and wear behaviour of micro alloyed ductile iron were investigated. Hardness, fracture, fracture toughness and wear tests were carried out on the ductile irons samples (D1, D2, D3, D4 and D5), containing micro alloyed nickel, molybdenum, copper and chromium in an amount of 0.2 % or less. They were characterized using optical metallurgical microscope and they contained pearlitic-ferritic matrix structure. They were subjected to wear test at room temperature based on pin-on-disk operation. Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Similar outcome was achieved with the use of manganese, nickel, molybdenum, and copper as micro alloying addition, as long as the composition of these elements did not exceed 0.5% [9]. It has been reported that optimal selection of combinations of Mo, Cr, Ni and Cu as micro alloying addition in ductile irons, results in improved strength, toughness and wear resistance [10,11]. However, the effect of these micro alloying additions on the damping properties of ductile irons has not come under scrutiny.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Similar outcome was achieved with the use of manganese, nickel, molybdenum, and copper as micro alloying addition, as long as the composition of these elements did not exceed 0.5% [9]. It has been reported that optimal selection of combinations of Mo, Cr, Ni and Cu as micro alloying addition in ductile irons, results in improved strength, toughness and wear resistance [10,11]. However, the effect of these micro alloying additions on the damping properties of ductile irons has not come under scrutiny.…”
Section: Introductionmentioning
confidence: 56%
“…The procedures adopted for the production of the ductile irons have been reported in details by Omole et al [10,11]. The process summarily, involved utilization of grey cast iron scrap as base metal, while ferro-molybdenum (72%), ferro-chrome (64% Cr), copper and nickel, were utilized as micro alloying additions.…”
Section: Materials and Methods Ductile Irons Productionmentioning
confidence: 99%